Mihaela Bîrladeanu, M. Iliescu, Liliana Macarie, Ioana Nichita, Mariana Ploae-Hanganu, Marius Sala, María Theban, Ioana Vintila-Radulescu. Coordonator: Marius Sala. Vocabularul reprezentativ al limbilor romanice. - Montes Giraldo, José Joaquín (Thesavrvs, 2023)
Reseña de libros.